Pattern of Maxillofacial fracture in Western and Central Nepal: An experience in 3 tertiary level health institutions - Subedi, S; Shrestha, B; Adhikari, RB (Journal of College of Medical Sciences-Nepal, 2015)
BACKGROUND: There are only few studies regarding the pattern and causes of maxillofacial fractures till date in Nepal and no such study in western and central Nepalese population has been conducted. The purpose of this study, therefore, was to describe the causes and the pattern of maxillofacial fractures in western and central part of Nepal over the period of 5 years. MATERIAL AND METHODS A retrospective analysis of maxillofacial fractures was conducted on 328 patients who were treated in the department of maxillofacial surgery. Data was extracted and analyzed based on age, sex, cause of injury and anatomic location. RESULT Young males of 3rd decade of life most commonly sustained the maxillofacial trauma. The commonest site involved was the zygomatic complex (42%) when only mid face fractures was considered and parasymphysis (32%) when only mandible was considered.The most common cause of injuries was road traffic accidents (289 patients; 88.1%) followed by interpersonal violence (25 patients; 7.6 %) and falls accounting for 4.2% of the all injuries. CONCLUSION The findings of this study suggest the need for expansion of the motorway network, ensuring compliance of strict traffic rules and regulations, replacing old vehicles without safety measures and implement school education in alcohol abuse. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 8-13